2015
DOI: 10.1002/adfm.201501712
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Multifunctional Platform Based on Strong, Intrinsically Photoluminescent and Antimicrobial Silica‐Poly(citrates)‐Based Hybrid Biodegradable Elastomers for Bone Regeneration

Abstract: Biodegradable biomaterials with intrinsically multifunctional properties such as high strength, photoluminescent ability (bioimaging monitoring), and antimicrobial activity (anti‐infection), as well as high osteoblastic differentiation ability, play a critical role in successful bone tissue regeneration. However, fabricating a biomaterial containing all these functions is still a challenge. Here, urethane cross‐linked intrinsically multifunctional silica‐poly(citrate) (CMSPC)‐based hybrid elastomers are develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 86 publications
(66 citation statements)
references
References 41 publications
0
66
0
Order By: Relevance
“…These hybrid elastomers still have the intrinsic problem of poor interface intensity between the inorganic phase and polymers. Therefore, our group introduced bioactive silica into PCD elastomers through a one-step thermal polymerization method [30,31,78,79]. The inorganic silica phase was bonded with the PCD polymer chain through covalent bonds.…”
Section: Synthesis and Properties Of Hybrid Polymersmentioning
confidence: 99%
See 3 more Smart Citations
“…These hybrid elastomers still have the intrinsic problem of poor interface intensity between the inorganic phase and polymers. Therefore, our group introduced bioactive silica into PCD elastomers through a one-step thermal polymerization method [30,31,78,79]. The inorganic silica phase was bonded with the PCD polymer chain through covalent bonds.…”
Section: Synthesis and Properties Of Hybrid Polymersmentioning
confidence: 99%
“…The inorganic silica phase was bonded with the PCD polymer chain through covalent bonds. The resulting hybrid polycitrate-silicon (PCS) elastomers demonstrated significantly improved elastomeric behavior, mechanical strength and cellular biocompatibility (Figure 7) [30]. SBGS-based PGS hybrid elastomers were also fabricated successfully through the direct hybridization of SBGS and PGS solution [29].…”
Section: Synthesis and Properties Of Hybrid Polymersmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, poly (citrate) (PC)‐based polymers have been gaining great interest in biomedical application such as tissue regeneration and gene delivery, due to their high biocompatibility, controlled biodegradation, and low cost . In previous study, our group developed a series of highly elastomeric PC‐based hybrid polymers, demonstrated their potential biomedical applications including bone tissue repair and gene delivery in vitro and in vivo . However, the conventional PC polymer shows the poor hydrophilicity and photoluminescent property, which limit their promising application in live cell imaging.…”
Section: Introductionmentioning
confidence: 99%